Decide : work smarter, reduce your stress and lead by example - McClatchy, Steve, 1968- (Wiley, 2014)
"How to make better decisions and achieve your goalsWhat shapes a person's career and life, and defines them as a leader? Their decisions. We all want to be more productive and deliver our best results. But doing this effectively--and consistently over time--is a significant challenge. Managing it all is hard, and leading in today's hyper-paced world is even harder. The good news is that leadership expert Steve McClatchy makes it easier. In Decide, McClatchy--who works with Fortune 1000 people every day to help them achieve outstanding levels of performance--shows you how to cut through the complexities and excuses to start realizing real gains simply by changing one thing: the way you make decisions. With McClatchy's help, you can quickly begin to: Use the time you have each day to move your business and your life forward Make decisions that yield better results Waste less time, reduce stress and regain balance Again and again, McClatchy has helped people learn for themselves how great decision-making habits yield a lifetime of accomplishments. Follow McClatchy's no-nonsense and practical approach, and you'll soon manage--and even lead--at your highest level of personal performance"--